Hyderabad, British India, and the world Muslim networks and minor sovereignty, c. 1850-1950 - Beverley, Eric Lewis (Cambridge University Press, 2015)
This examination of the formally autonomous state of Hyderabad in a global comparative framework challenges the idea of the dominant British Raj as the sole sovereign power in the late colonial period. This book recasts the political geography of late imperialism and historicises Muslim political modernity in South Asia and beyond.